COMPARISON OF STS-PCR, RAPD-PCR, DAMD-PCR FOR PHOLOMIS, MELISSA, ORIGANUM, ROSMARINUS AND SIDERITIS SPECIES - Ince, A. G.; Karaca, M.; Onus, A. N.; Baktir, I. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
A large number of medicinal and aromatic plant species naturally grown in the Mediterranean basin of Turkey are endemic to this region. Genetic studies of these species; however, fall behind the other cultivated species. The last three decades witnessed the development of tremendous number of molecular approaches such as DNA techniques to be used in germplasm evaluation and plant genetic analysis. DNA markers have been used in plant molecular ecology, taxonomy and plant breeding studies. The use of these DNA techniques are extremely important for those difficult plant species with limited reliable taxonomic characters. Random amplified polymorphic DNA (RAPD-PCR), directed amplification of minisatellite region DNA (DAMD-PCR) and Sequence Tagged Sites (STS-PCR) were used to determine which of these markers provide repeatable and higher level polymorphism information content values on five different genus; Pholomis, Melissa, Origanum, Rosmarinus and Sideritis. Genomic, chloroplast and mitochondrial DNAs of two species of Sideritis, Origanum, and one species of Pholomis, Melissa, Rosmarinus and Teacrium were extracted and analyzed. Studies clearly indicated that STS–PCR markers of mitochondria and chloroplast were less polymorphic based on their PIC values. On the other hand the PIC values of DAMD-PCR and RAPD techniques were equally similar. The numbers of amplicons were lower in DAMD-PCR than that of the RAPD-PCR. In conclusion the results of the present study indicated that DAMD-PCR and RAPD-PCR were equally effective in differentiation of the species of Lamiaceae. Although STS showed lower polymorphism, they are extremely valuable in identification of naturally occurring inter-specific hybrids